ANALISIS KELAYAKAN INVESTASI UNTUK PENGEMBANGAN USAHA PADA RUMAH KOS WISDOM PLACE DI GADING SERPONG, KABUPATEN TANGERANG - Aritonang, Ramona; Agus Munandar (Accounting Profession Journal (APAJI), 2025)
The most fundamental human needs are clothing, food, and shelter, and these three needs must be met by every individual. The term "shelter" refers to the need for a place to live, including for migrants. Wisdom Place Boarding House, as a provider of boarding rooms, wants to develop its business by investing and increasing room capacity to rent out more rooms. Every investment inevitably involves risks that must be considered before making an investment. Wisdom Place Boarding House conducts a feasibility analysis study for investment by using a business feasibility study. By using qualitative methods and describing the results descriptively, there are two data sources used for the Wisdom Place boarding house investment feasibility study: primary data through observation and interviews, and secondary data by reviewing documents obtained from journals, websites, e-books, and news articles related to this research. The business feasibility study aspects conducted for Wisdom Place Boarding House include market and marketing aspects, management and organizational aspects, technical and technological aspects, and financial aspects. The conclusion of the research is that Wisdom Place Boarding House is feasible for investment by adding 10 rooms on the third floor. Keywords: Investment, Business Feasibility Study, Wisdom Place Boarding House, Qualitative Method.